2019
DOI: 10.3390/s19051189
|View full text |Cite
|
Sign up to set email alerts
|

An LC Wireless Microfluidic Sensor Based on Low Temperature Co-Fired Ceramic (LTCC) Technology

Abstract: This work reports a novel wireless microfluidic biosensor based on low temperature co-fired ceramic (LTCC) technology. The wireless biosensor consists of a planar spiral inductor and parallel plate capacitor (LC) resonant antenna, which integrates with microchannel bends in the LTCC substrate. The wireless response of the biosensor was associated to the changes of its resonant frequency due to the alteration in the permittivity of the liquid flow in the microchannel. The wireless sensing performance to differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 44 publications
0
23
0
Order By: Relevance
“…The possibility of integrating electronic wirings, magnetic or piezoelectric components, and thick-film passive elements in 3D mechanical structures complements the benefit array of this technology. Therefore, LTCC is widely used in environmental resisted, multilayer, high frequency circuits, sensors, actuators, micro-systems, etc [8,[31][32][33]. Since micro-fluidic channel and chamber systems together with actuators, sensors, and electronic circuits can be bound in a common multilayer structure, the great opportunity to create sophisticated platforms for micro-reactors appears.…”
Section: Low Power Ltcc Flow Sensormentioning
confidence: 99%
“…The possibility of integrating electronic wirings, magnetic or piezoelectric components, and thick-film passive elements in 3D mechanical structures complements the benefit array of this technology. Therefore, LTCC is widely used in environmental resisted, multilayer, high frequency circuits, sensors, actuators, micro-systems, etc [8,[31][32][33]. Since micro-fluidic channel and chamber systems together with actuators, sensors, and electronic circuits can be bound in a common multilayer structure, the great opportunity to create sophisticated platforms for micro-reactors appears.…”
Section: Low Power Ltcc Flow Sensormentioning
confidence: 99%
“…Microfluidic relative permittivity sensors have great potential for fluid discrimination and composition determination [1,2]. Applications include the detection of medicine composition in medical infusion pumps [3], single-cell impedance cytometry [4,5], composition detection in flow chemistry [6,7], production monitoring of polymers [8], void-fraction measurement in two-phase flow [9,10], and measurement of glucose concentration in water [11,12] or water content in oil [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, the assembly of low temperature co-red ceramics (LTCC) with discrete sensors, resistors, and inductors into a single monolithic chip component can achieve multifunctional performance and promote miniaturization in the printed circuit board (PCB) during assembly. [1][2][3][4] For example, Wang et al 5 reported a novel V-modied Li 3 Mg 2 NbO 6 ceramics with outstanding microwave dielectric properties and can reach densication at 900 C. Li et al 6 synthesized the In-doped Mg-Cd ferrite at low sintering temperature using Bi 2 O 3 additive. These efforts make these ceramics promising candidates for LTCC applications.…”
Section: Introductionmentioning
confidence: 99%